2018
DOI: 10.1111/jbi.13182
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of a ‘great speciator’ (Aves:Edolisoma tenuirostre) reveals complex dispersal and diversification dynamics across the Indo‐Pacific

Abstract: Aim We derive a new phylogenetic framework of the Indo‐Pacific avian genus Edolisoma based on a dense taxon sampling and use it in an explicit spatiotemporal framework to understand the history of intraspecific diversification dynamics in a ‘great speciator’, the Cicadabird Edolisoma tenuirostre/remotum complex. Location The Indo‐Pacific island region, Australia and New Guinea. Taxon Corvoid passerine birds (Passeriformes). Methods We used Bayesian phylogenetic methods (beast) to construct a time‐calibrated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 52 publications
6
38
1
Order By: Relevance
“…The lack of diversification in such a widespread bird seems remarkable, particularly considering the level of diversification in the Collared Kingfisher species complex (Andersen et al 2015b) and several other vagile taxa (Cibois et al 2014, Andersen et al 2015a, Garcia-R et al 2017) over the same area as the Sacred Kingfisher's range. However, these findings for the Sacred Kingfisher tally with those of Pedersen et al (2018), who found that populations of the Common Cicadabird species complex (E. t. pellingi and E. t. obiense) remained morphologically and genetically similar, despite being separated by 500 km of deep ocean. One population of the Common Cicadabird (E. t. tenuirostre) also migrates between Australia and New Guinea (Taylor & Kirwan 2018).…”
Section: Our Results Demonstrated a Clear Split In Collaredmentioning
confidence: 72%
See 1 more Smart Citation
“…The lack of diversification in such a widespread bird seems remarkable, particularly considering the level of diversification in the Collared Kingfisher species complex (Andersen et al 2015b) and several other vagile taxa (Cibois et al 2014, Andersen et al 2015a, Garcia-R et al 2017) over the same area as the Sacred Kingfisher's range. However, these findings for the Sacred Kingfisher tally with those of Pedersen et al (2018), who found that populations of the Common Cicadabird species complex (E. t. pellingi and E. t. obiense) remained morphologically and genetically similar, despite being separated by 500 km of deep ocean. One population of the Common Cicadabird (E. t. tenuirostre) also migrates between Australia and New Guinea (Taylor & Kirwan 2018).…”
Section: Our Results Demonstrated a Clear Split In Collaredmentioning
confidence: 72%
“…Mayr and Diamond (2001) developed the 'great speciator' concept for their study system in Northern Melanesia to describe a group of birds with high inter-island geographical variation, including diverse taxa found across many islands (e.g. In recent years modern molecular methods have enabled researchers to begin to uncover the intricate evolutionary histories of the 'great speciators', showing them to be complexes of closely related species (Andersen et al 2013, Irestedt et al 2013, Pedersen et al 2018. Because of their wide ranges and multiple distinct populations, the 'great speciators' have provided ideal study systems for developing many key concepts in evolutionary biology (Mayr 1942, Diamond 1974, Diamond et al 1976).…”
mentioning
confidence: 99%
“…Elevational ranges were obtained from Taylor () and following Pedersen et al. () we assigned all species into one of three elevational range classes: species usually inhabiting (a) coastal, (b) lowland or (c) montane areas (see Table S1.3 in Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…These species may be undifferentiated and continuously distributed across all small islands in a region, often including coastal and other marginal habitats on larger islands within their range. Diamond (, ) was not able to assess the temporal mode of supertramp evolution, but today we know, from molecular phylogenetic analyses, that the supertramp stage can extend over 700 kyr (Jønsson et al., ; Pedersen, Irestedt, Joseph, Rahbek, & Jønsson, ). Rapid sweepstake colonizations followed by a reduction in dispersal ability and subsequent population differentiation across the range of a widespread ‘tramp’ species (isolation by distance) may then result in a stage where the species is recognized as a ‘great speciator’ (stage II), which represents another ‘extreme’ diversification stage (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation